2022
DOI: 10.3390/ijerph19095394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Hypobaric Hypoxia Exposure on Cardiovascular Function in Unacclimatized Healthy Subjects: A “Rapid Ascent” Hypobaric Chamber Study

Abstract: Background: This study aimed to observe the effects of a fast acute ascent to simulated high altitudes on cardiovascular function both in the main arteries and in peripheral circulation. Methods: We examined 17 healthy volunteers, between 18 and 50 years old, at sea level, at 3842 m of hypobaric hypoxia and after return to sea level. Cardiac output (CO) was measured with Doppler transthoracic echocardiography. Oxygen delivery was estimated as the product of CO and peripheral oxygen saturation (SpO2). The brach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In particular, a reduction in SpO 2 has been found to result in a dramatic increase in the rate of hemoglobin autoxidation [ 40 , 41 , 42 ]. Therefore, because of the hypoxic exposition, oxidative stress might result from an increase in the autoxidation rate of partially oxygenated hemoglobin—particularly to that formed at the microcirculation level, as shown by the post-occlusion hyperhaemia reaction during acute hypoxia exposure [ 43 ]. This hypothesis seems to be confirmed by the reported significant inverse relationship between SpO 2 and the ROS production rate presently detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a reduction in SpO 2 has been found to result in a dramatic increase in the rate of hemoglobin autoxidation [ 40 , 41 , 42 ]. Therefore, because of the hypoxic exposition, oxidative stress might result from an increase in the autoxidation rate of partially oxygenated hemoglobin—particularly to that formed at the microcirculation level, as shown by the post-occlusion hyperhaemia reaction during acute hypoxia exposure [ 43 ]. This hypothesis seems to be confirmed by the reported significant inverse relationship between SpO 2 and the ROS production rate presently detected.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the altitude and time of exposure chosen tended to simulate the conditions experienced by mountain lovers during a single-day trip in alpine environments. Moreover, the study might help to highlight some key elements in acclimatization, as well as being of help for all those people who work at high altitudes without sufficient time to acclimatize, such as mountain rescue personnel/teams operating on helicopters during emergency medical operations (i.e., pilots, mountain rescuers and medical doctors) [ 43 ]. Finally, our EPR methods could be applied as a standard procedure in mountain medicine for studying changes induced by hypoxia due to acute and chronic high altitude stays.…”
Section: Discussionmentioning
confidence: 99%
“…Increased report of headache during hypoxia for females is particularly relevant in an aeromedical context because headache frequency is a major factor influencing suitability for aviation service ( Hesselbrock and Haynes, 2020 ). Hormonal contraceptive use is related to cerebrovascular and cognitive changes, which could be further altered during hypoxic conditions; future works should explore the association between hormonal contraceptive use and headache reports ( O’Brien et al, 2020 ; Theunissen et al, 2022 ). The risk of migraine recurrence is also an important factor for aeromedical readiness, particularly in pilot applicants who incur a substantial training investment.…”
Section: Discussionmentioning
confidence: 99%
“…(barometric pressure of 692 mBar) in Caspana, Chile. Acute exposure was defined as the first 24 h from arrival to altitude ( Pollock et al, 1993 ; Testing, 2015 ; Theunissen et al, 2022 ) in our study. During the first day of arriving at HA, the participants were instructed about the measurement procedures: investigators showed the Monark cycle ergometer in detail, accessories of the portable high-resolution spiroergometry system (MetaLyzer ® 3B-R2, CORTEX, Germany) such as a mask, spirometry sensor, gas analyzer, flow and volume sensor, and chest strap with a heart rate monitor (H10, POLAR, Finland).…”
Section: Methodsmentioning
confidence: 99%